DAMPAK KENAIKAN TARIF PPN DAN KEMUDAHAN TRANSAKSI DIGITAL TERHADAP GAYA HIDUP KONSUMSTIF MASYARAKAT JAKARTA DI USIA 20 – 30 TAHUN - Rizma Arindy; Fitrawansyah; Dyah Shinta Kusumaningtyas (Universitas La Tansa Mashiro, 2025)
This research purpose to examine the effect of increasing Value Added Tax (VAT) rates and the development of digital transactions, which are two important factors that influence the consumption patterns of urban communities, especially the productive age group. The method used was descriptive quantitative with purposive sampling technique and involved 100 respondents. Data was collected through a questionnaire using a 5 point Likert scale and analyzed using multiple linear regression. The research results show that the two independent variables, both partially and simultaneously, have a significant effect on consumer lifestyle. The ease of digital transactions has a more dominant influence than the increase in VAT rates. These findings confirm that digitalization has a strong role in encouraging consumer behavior, even amidst fiscal policy pressures. This research contributes to the development of tax policy strategies that are adaptive to the consumption behavior of the younger generation as well as strengthening digital financial literacy in society